Positivity level predicts better health and mental health among adults - Qamar, Shazeen; Yaqoob, Nazia (Journal of Current Health Sciences, 2023)
The aim of this study is to predict positivity impact on mental health and overall health of adult students. Objective of study: To explore the relationship between adult positivity connection with mental health. Predict the relationship between positive behaviour and its impact on mental health in adults. Check significance gender difference of adult positivity as a predictor of better health and mental health. Research Design: In this study, a correlational research design was employed. Sampling Techniques: The sample was taken using by purposive sampling technique. Sample: The sample (N=200; 100 males, 100 females) of the study includes Government and private university students from the city of Faisalabad. Participants in the study ranged in age from 18 to 35 years old. Tool: A reliable tool of positivity, Rosenberg self-esteem, life satisfaction and BBC subjective well-being scales have used to measure the variables. Statistically analyse: The data have statistically analyse descriptive statistics, correlation, independent sample T-test, and regression run by using the SPSS software, to test the hypothesis of the study. Results: The Statistical Package for Social Sciences was used to analyse the data (SPSS, V 12.0). For the analysis, a significance level of 0.05, 0.01 was employed.